Sustainable bio-energy production models for eradicating open field burning of paddy straw in Punjab, India. (15th May 2017) - Trivedi, Abhinav; Verma, Amit Ranjan; Kaur, Supreet; Jha, Bhaskar; Vijay, Vandit; Chandra, Ram; Vijay, Virendra Kumar; Subbarao, P.M.V.; Tiwari, Ratnesh; Hariprasad, P.; Prasad, Rajendra
Abstract: The mechanized harvesting of paddy crop has led into open field burning of paddy straw. Burning of million tonnes of paddy straw releases huge potent greenhouse gases which creates perturbations to regional atmospheric chemistry. This paper presents a case study on utilization of paddy straw for power generation through biomethane and bioethanol production on commercial scale and improved biomass cookstove on domestic scale. Three scenario (biomethane, bioethanol and pellet for improved biomass cookstove) have been compared for their energy economics and emission. It has been revealed that if paddy straw is not being burned, it can be effectively utilized for biomethanation and bioethanol production which can yield energy equivalent of 8.0 GJ/tonne and 5.6 GJ/tonne, respectively, while pelletized paddy straw can be used in improved biomass cookstoves to meet out thermal cooking energy requirement with reduced indoor air pollution. The analysis further revealed that biomethanation of paddy straw reduces net global warming potential by 2750 CO2 e kg emissions/tonne. However, bioethanol production showed net global warming potential reduction of 2549 CO2 e kg emissions/tonne. The pelletization of paddy straw for improved cookstove showed net global warming potential reduction of 2459 CO2 e kg emissions/tonne. Highlights: Biomethane production from paddy straw showed a total energy yield of 8.0 GJ/tonne. Bioethanol production from paddy straw showed a total energy yield of 5.6 GJ/tonne. Biomethanation route showed net global warming potential reduction of 2750 CO2 e kg emissions/tonne. Pelletization for improved cookstove showed net global warming potential reduction of 2459 CO2 e kg emissions/tonne. Bioethanol route showed net global warming potential reduction of 2549 CO2 e kg emissions/tonne.